Astronomical forcing variations of the Upper Dalan Member (Late Permian) in the South Pars gas field, Persian Gulf, Iran. (15th April 2021) - Falahatkhah, Omid; Kadkhodaie, Ali; Ciabeghodsi, Ali Asghar; Wood, David A.
Graphical abstract: Highlights: Orbital cycles detected the in the Late Permian strata of South Pars gas field Iran. Prolific gas reservoirs units K1 to K4 units) formed over a time interval of 4.8 ± 0.3 Myr. Sediment accumulation rates of the Upper Dalan Member range from 3.5 to 18 cm/kyr. Depositional duration of the Upper Dalan Member estimated to be 3.2 Myr ± 0.2 Myr. Eight 405-kyr long-eccentricity cycles were identified from well log analysis. Abstract: The Late Permian sedimentary succession in the Iranian offshore Persian Gulf, formed under arid paleoclimate conditions, has been poorly studied in terms of astronomical forcing evidence. In this study, petrophysical logs are applied as paleoclimate proxies. They are used to investigate the astronomical forcing of the arid paleoclimate during the Late Permian together with the sediment accumulation rates (SAR) of the Upper Dalan Member (UDM) in two wells drilled in the South Pars gas field. Evidence of Milankovitch cycles (eccentricity, obliquity, and precession) was detected in both of the studied wells. By application of a combination of different methods (e.g., spectral analysis, COCO/eCOCO analysis), the SAR of the UDM was estimated to be in the range of 3.5 to 18 cm/kyr. Based on the 405 kyr long-eccentricity cycles extracted from the spectral gamma ray (SGR) logs, a floating astronomical time scale (ATS) of 3.2 ± 0.2 Myr was established for the UDM. This is equivalent to the depositional duration of the UDM in the studied wells. The Kangan Formation and UDM (K1 to K4 units) of southwestern and offshore of Iran were deposited during an astronomical duration of 4.8 ± 0.3 Myr. Additionally, the accumulation of organic matter in the studied reservoir units was compared with the SAR. The effects of SAR on the total organic carbon (TOC) variations were detected and correlated in four different segments of the UDM.